Climate change and the public health imperative for supporting migration as adaptation - Hannah Marcus; Liz Hanna; Peter Tait; Sheila Stone; Chadia Wannous (Elsevier, 2023)
In an era of accelerating global climate change, human mobility has reached unprecedented levels. While it is acknowledged that many cases of human migration in the context of climate change are forced or involuntary, particularly where adaptation measures have failed to achieve sufficient resiliency of communities against impending slow- and sudden-onset disasters. There are also many cases where migration is, itself, a voluntary adaptive measure to secure otherwise unattainable physical safety and life-sustaining resources. It is in these cases that migration can be viewed as adaptation. Under the right policy conditions, it is possible for such adaptive migration to save countless lives. Moreover, it can achieve remarkable health and well-being gains for otherwise vulnerable communities residing on environmentally degrading lands and disproportionately suffering from the health impacts of climate change. While several activists have spoken loudly on the topic of climate migration, emphasizing the human rights imperative for supportive global policy action, the public health community has not been equally vocal nor unanimous in its stance. This paper, a product of the World Federation of Public Health Associations (WFPHA) Environmental Health Working Group, aims to rectify this gap, by analyzing adaptive climate migration through a public health lens. In doing so, it argues that creating an enabling environment for adaptive climate migration is not just a human rights imperative, but also a public health one. This argument is supported by evidence demonstrating how creating such an enabling environment can synergistically support the fulfillment of key public health services and functions, as outlined under the internationally endorsed Global Charter for the Public's Health of the WFPHA.